Confederate Heritage Organizations and Confederate Monument Removal - Jess Phelps; Jessica Owley (Washington University Journal of Law and Policy, 2023)
Prominent players in the debates concerning the removal and relocation of Confederate monuments are the multitude of Confederate heritage organizations. These organizations challenge the removal of Confederate monuments and are frequently successful in their efforts. Often times, these organizations possess a legal interest in the disposition of Confederate monuments either because they have funded the erection of such monuments, worked to maintain monuments, or have residual ownership claims. This Article seeks to highlight the role of Confederate heritage organizations in monument removal and relocation debates. The Authors explore the origins of Confederate monuments, why statues are removed now, the history of heritage organizations, and the operation of such organizations in response to removal attempts. The Authors argue that it is important for communities involved in removal efforts to (1) understand the objectives of heritage groups, (2) understand the history of the monument (3) understand the heritage organizations as an entity, (4) account for the community’s goal and long term impacts of removal, and (5) consider the implications of transferring monuments to heritage organizations. Ultimately, the Article encourages communities to become familiar with heritage organizations in order to understand and account for their influence in removal and relocation decisions.
Keywords: Confederate Monuments; Confederate Heritage; Statue; Monument Ownership; Monument Removal